PENERAPAN ASAS KEPASTIAN HUKUM DALAM PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN BOYOLALI - , RINI SULISTIYANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Acquisition duty of right on land and building (BPHTB) is local tax that its imposing procedure used self assessment principle in which tax obligation that tax payer should pay based on transaction value of NJOP and the tax due should be calculated immediately without waiting for tax assessment. In practice, there are many difference between price agreed by parties that price submitted to DPPKAD. Tax payer report is submitted through SSPD and followed up with validation done by DPPKAD based on Local regulation Number 2 of 2011 that is further regulated in Article 12 of Regent Regulation number 8 of 2011 on procedure of validation on BPHTB tax due. Implementation of validation system induce problem related to Article 12 paragraph b âmatching Land and Building NJOP written down in SSPD and Land and Building NJOP per meter square in land and building tax databaseâ. Unopened DPPKAD on the database is contradict to Law number 14 of 2008 concerning Public Information openness and lead to legal uncertainty. It is juridical empirical research done by literary study and field study using interview guide. Data was analyzed using deductive method, so this research was expected to result in accountable conclusion. The research focus on legal uncertainty on collecting BPHTB particularly in validation system that is caused by two factors of DPPKAD reducing NJOP in SPPT with objective of reducing tax evasion by tax payer and review of NJOP adjustment that is often late resulting in difference between transaction price and market price. Not database cause underpaid tax assessment done with assumption. Effort done by DPPKAD is dissemination in field based on economic and geographical condition and the institution should make fixed procedure on database for guidance in BPHTB validation process and accessible for tax payer. Parameter in determining BHPTB tariff should be informed to public before or after determination of NJOP.